Micronutrients intake as risk factor of stunting in toddlers aged 6-24 months in Kintamani District, Bali - Prabandari, Anak Agung Sagung Mirah; Sirait, Josephine Claudia; Wijanadi, M.Candra; Harimawan, Agustinus I Wayan (World Nutrition Journal, 2024)
Reducing stunting is a priority program for the Indonesian government. Kintamani District is one of the areas in Bali Province with a stunting prevalence above the provincial average. Micronutrients play an essential role in growth and development, but their intake in children is often overlooked. This study aimed to investigate micronutrient intake as a risk factor for stunting in toddlers aged 6-24 months in the Kintamani district, Bali.